2020
DOI: 10.3390/ijms21041312
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Residualizing Properties of the Radiolabel on Radionuclide Molecular Imaging of HER3 Using Affibody Molecules

Abstract: Human epidermal growth factor receptor type 3 (HER3) is an emerging therapeutic target in several malignancies. To select potential responders to HER3-targeted therapy, radionuclide molecular imaging of HER3 expression using affibody molecules could be performed. Due to physiological expression of HER3 in normal organs, high imaging contrast remains challenging. Due to slow internalization of affibody molecules by cancer cells, we hypothesized that labeling (HE)3-ZHER3:08698-DOTAGA affibody molecule with non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Among the radiometal labels, radiocobalt labeled (HE) 3 -Z HER3:08698 -DOTA has shown to be the most promising variant, for the first time exceeding a tumor-to-liver ratio of one, a prerequisite for the detection of HER3 expressing metastases in liver [ 265 ]. The use of non-residualizing iodine labeled further increased this ratio to 2.4 (4 h pi), a similar ratio to what was achieved by co-injection of the affibody trimer [ 107 , 267 ]. However, the tumor uptake of [ 125 I]I-PIB-(HE) 3 -Z HER3:08698 -DOTAGA was three times lower than the tumor uptake of [ 111 In]In-(HE) 3 -Z HER3:08698 -DOTAGA and decreased appreciably from 4 to 24 h [ 107 ].…”
Section: Her3 Imagingmentioning
confidence: 68%
See 2 more Smart Citations
“…Among the radiometal labels, radiocobalt labeled (HE) 3 -Z HER3:08698 -DOTA has shown to be the most promising variant, for the first time exceeding a tumor-to-liver ratio of one, a prerequisite for the detection of HER3 expressing metastases in liver [ 265 ]. The use of non-residualizing iodine labeled further increased this ratio to 2.4 (4 h pi), a similar ratio to what was achieved by co-injection of the affibody trimer [ 107 , 267 ]. However, the tumor uptake of [ 125 I]I-PIB-(HE) 3 -Z HER3:08698 -DOTAGA was three times lower than the tumor uptake of [ 111 In]In-(HE) 3 -Z HER3:08698 -DOTAGA and decreased appreciably from 4 to 24 h [ 107 ].…”
Section: Her3 Imagingmentioning
confidence: 68%
“…The use of non-residualizing iodine labeled further increased this ratio to 2.4 (4 h pi), a similar ratio to what was achieved by co-injection of the affibody trimer [ 107 , 267 ]. However, the tumor uptake of [ 125 I]I-PIB-(HE) 3 -Z HER3:08698 -DOTAGA was three times lower than the tumor uptake of [ 111 In]In-(HE) 3 -Z HER3:08698 -DOTAGA and decreased appreciably from 4 to 24 h [ 107 ].…”
Section: Her3 Imagingmentioning
confidence: 68%
See 1 more Smart Citation
“…The focus of this study was on the dimerization of EGFR and HER2, as both receptors have pivotal clinical importance, but several other possible dimerization partners, from the same HER family, as well as from other receptor kinase subfamilies, can also interact with these receptors [71]. Quantification of such rather "promiscuous" interactions of EGFR and HER2 might be desired in the future, and could be achieved by exchanging EGF or the anti-HER2 affibody with other specific receptor ligands, for instance insulin-like growth factor I [72], or another engineered binding peptide, such as an anti-HER3 affibody [73]. Depending on the availability of specific, small binding molecules, the method could be even extended to measure a broad range of endogenous membrane protein interactions, and it can possibly be combined with a protocol we recently developed for the detection of HER2 in dissociated tumor cells from patient FFPE tissue samples [64].…”
Section: Discussionmentioning
confidence: 99%
“…Slow internalization in vitro is not always translated into slow internalization in vivo [36], because cancer cells in vivo are exposed to a broader spectrum of signaling substances than it is possible to mimic in vitro. However, the results of the biodistribution experiments (Figure 5) showed that uptake of [ 125 I]I-PIB-Ec1 in ovarian cancer xenografts (3.1 ± 0.7 and 2.1 ± 0.3 %ID/g at 6 h after injection, for SKOV-3 and OVCAR-3 xenografts, respectively) was in the same range as for pancreatic cancer BxPC-3 xenografts at the same time point (3.2 ± 0.8 %ID/g) [29].…”
Section: Discussionmentioning
confidence: 99%